Epidemiology of Head Lice: (Pediculushumanus capitis) among Primary Schoolchildren in Misurata, Libya (Journal of Academic Research, 2025)
Infestation of head lice (Pediculus humanus capitis) is a common ectoparasitic infection in schoolchildren, causing a public health problem, which is neglected in Libya. The study aimed to conduct an epidemiological statistical study of the prevalence of pediculosis capitis infestation among primary schoolchildren in Misurata City and to determine risk factors associated with the infestation. The study was conducted from March to May 2023. 1006 primary schoolchildren were selected randomly and screened for head lice by visual scalp examination. A questionnaire was used to collect data on sociodemographic status. Statistical analysis was conducted using the SPSS software package. The chi-square test was used to assess the statistical significance. The Results showed Head lice infestation rate was 12.8%, it was higher in girls (18.9%) than boys (5.0%), and it was higher in public schools (13.6%) than private schools (8.2%). The infestation rate among schools ranged from 6.6% to 22.7%. There was a significant association between pediculosis infestation and genders (P=0.000), school grade (P=0.014), covered hair (P=0.000), hair softness (P=0.001), hair length (P=0.016), mother's job (P=0.000), father's lack job (P=0.015), place of residence (P=0.044), history of head lice infestation (P=0.000), and no significant difference to nationality, thick hair, presence of siblings in the same school, family size. In Conclusion Head lice infestation is a health problem in primary school girls of Misurata. Providing proper educational programs about pediculosis and prevention and improvement of socioeconomic status can be useful in reducing head lice infestation.